CONTENT ANALYSIS OF TWO ENGLISH TEXTBOOKS WRITTEN FOR THE 2013 CURRICULUM - Shafwati, Dian (2016)
The importance of textbooks in the learning processes has been indicated among others in the wide attention from various parties, including the government and private sector. This study examined two English textbooks which are written for the 2013 curriculum. It particularly aims to investigate whether the content of the two English textbooks for eleventh grade of Senior High School, which are written for the 2013 Curriculum, i.e. the official English textbook published by the government and a commercial English textbook published by a private publisher, fulfilling textbook evaluation criteria proposed by the experts. This study also aims to investigate the differences found between these English textbooks. This study is in general qualitative. It bases its analysis on the textbook evaluation criteria proposed by Cunningsworth (1995), Harmer (2007b), and BSNP. The results show that both textbooks meet the criteria of a good EFL textbook in terms of aims, sequence, grammar content, topics, clarity of instructions, as well as durability and appearance. However, some weaknesses are found in both textbooks in terms of approach and technique in presenting new items, lack of vocabulary content, and the absence of recycling and revision processes. Moreover, this study also reveals some differences between these two English textbooks with regard to skills treatment, practical considerations, and topic selection. The findings lead to the conclusion that in general the two English textbooks meet the criteria of good EFL textbooks and they are also relevant to the 2013 curriculum. Therefore, it is recommended that these two English textbooks be used as teaching resources but efforts should be made to compensate for some weaknesses found.;---- Pentingnya buku teks telah dalam proses pembelajaran telah menjadi perhatian besar diantara berbagai pihak, termasuk pemerintah dan pihak swasta. Penelitian ini meneliti dua buku teks bahasa Inggris yang ditulis untuk kurikulum 2013. Penelitian ini khususnya bertujuan untuk meneliti isi dari dua buku teks bahasa Inggris untuk kelas XI SMA, yang ditulis untuk kurikulum 2013, yaitu buku teks bahasa inggris resmi yang diterbitkan oleh pemerintah dan buku teks bahasa inggris komersial yang diterbitkan oleh swasta, memenuhi kriteria penilaian buku teks berdasarkan para ahli. Penelitian ini juga bertujuan untuk meneliti perbedaan yang ditemukan diantara kedua buku teks bahasa Inggris tersebut. Penelitian ini termasuk kedalam penelitian kualitatif. Penelitian ini berbasis pada kriteria penilaian buku teks yang dikemukakan oleh Cunningsworth (1995), Harmer (2007b), and BSNP. Hasil dari penilitian menunjukan bahwa kedua buku teks ini memenuhi kriteria buku teks EFL yang baik dalam hal tujuan, urutan, isi dari grammar, topic, kejelasan instruksi, juga keawetan dan penampilan. Namun, beberapa kelemahan juga ditemukan pada kedua buku ini dalam hal pendekatan dan teknik dalam menyajikan informasi baru, kurangnya materi vocabulary, dan tidak adanya proses recycling ada revision. Lebih lanjut, penelitian ini juga menemukan beberapa perbedaan diantar kedua buku teks ini dalam hal penyajian skill, pertimbangan praktis, dan pemilihan topic. Hasil dari penelitian ini mengacu pada sebuah kesimpulan bahwa pada umumnya kedua buku teks Bahasa Inggris ini memenuhi kriteria dari buku teks EFL yang baik serta mereka juga relevan dengan kurikulum 2013. Oleh karena itu, kedua buku ini direkomendasikan untuk digunakan sebagai sumber pembelajaran namun beberapa usaha harus dilakukan untuk mengkompensasi kelemahan yang ditemukan.